The Rendition of Semantic & Semiotic Expressions in Mourid Barghthouti’s Autobiography: An Ethnographic Account of a People - Ayman R. Nazzal (Modern Perspectives in Language, Literature and Education Vol. 10, 2021)
I saw Ramallah, is an autobiography of Mourid Barghouti, a Palestinian writer and poet. It is an honest and accurate account of a Palestinian who could not adapt to the changes that have taken place during his absenteeism. It can also be considered a precise manifestation of the national and political identity of the author. It is about the abandonment and loss that Palestinians feel both in Palestine and in the Diaspora. I saw Ramallah is the type of literary genre that won the admiration of Edward Said, who considered it as, "one of the finest existential accounts of Palestinian displacement that we now have." The primary objective of this study is to underlie the semantic and semiotic challenges in the rendition of this autobiography into English by Ahdaf Soueif, the celebrated Egyptian novelist and critic. I chose this autobiography as a case study on account that it embodies some interesting pragmatic and semiotic issues worthy of investigation and study. This study examines some of the translation strategies adopted by Ahdaf Soueif in handling the complexity posed by cultural-bound expressions since such expressions are very likely to pose a real challenge for the translator [1]. This study underlies the role of language in reflecting the realities of an entire community; all encompassed as facts, memories, imagination, and fiction.